Postdigital Visual Literacy: A Semiotic Perspective - Kearney, Richard (Auckland University of Technology, 2020)
Visual literacy, a literacy that involves the meaningful decoding of images, is often invoked when discussing environments rich with new media. Facebook, Instagram, YouTube; these platforms are image heavy. Major platforms such as these leverage the prosumer identity for economic means. The wider networking that the internet affords sees the intersection of the nominal democracy of participatory spaces with existing economic and social power structures. This increases the complexity of discourses of power that allow for meaning to emerge. Digital natives, students who grew up with networked technology as the norm, are often regarded as having a higher degree of visual literacy. This proposition, however, is not as simple as it seems on the surface. It is further problematised by postdigital theory. Postdigitality proposes that the distinction between digital and analogue, or online and offline, are arbitrary impositions upon the world. That arbitrariness challenges the essentialism inherent in the terminology ‘digital native’. Postdigital theory and visual literacy discourse have three major intersecting concerns: the permeability between classroom teaching and the ‘outside world’, the role of criticality, and socially generated knowledge and authority. A semiotic framework is employed in this research to reconcile postdigital theory within a reconstructed theory of visual literacy that meaningfully addresses the raised concerns. The semiotic theories of Charles Sanders Peirce, and the edusemiotic approach of Inna Semetsky, Andrew Stables, and others, inform an emancipatory vision of literacy, one that addresses the continuity between social lived experience and the classroom; and online and offline worlds. Peirce’s theories of habit and habit change afford an approach to critical literacy that goes beyond a habit of scepticism. The resulting theory of visual literacy that is proposed in the reconstruction has two components: use literacy and critical literacy. Use literacy is the ability to communicate using images but acknowledges that there is no one way to do this. As a result, notions of cultural literacy and institutionally mandated literacy, rather than standing in opposition, are folded into one another. The implication of this is that classroom practice should incorporate students’ socially generated visually literacies, alongside teaching established conventions. The critical dimension of visual literacy, proposed by this research, involves aiming to develop students’ semiotic awareness to resist habitual viewing. This dimension should not be relegated to an extension task but be taught alongside the development of a rich use literacy.
Keywords: Visual literacy; Postdigital; Semiotics; Digital learning; Peircean semiotics; Edusemiotics